EXPLORING THE IMPACT OF PIM 3 SCORE ON CLINICAL DECISION-MAKING: A SINGLE-CENTER STUDY - HAREESH; HASEEB, ABDUL; MALASHETTY, SHARANABASAPPA (International Journal of Current Pharmaceutical Research, 2024)
Objective: In the dynamic landscape of healthcare, the quest for precision in clinical decision-making is pivotal. The Pediatric Index of Mortality 3 (PIM 3) score has emerged as a crucial metric in predicting mortality risk among critically ill children, shaping medical choices in pediatric intensive care units. Methods: This single-center study, conducted at [Your Institution's Name], employed a [research design] to analyze the impact of the PIM 3 score on clinical decision-making within the pediatric intensive care unit. The study included [number] critically ill pediatric patients aged 1 mo to 18 y, with data extracted from electronic health records. Statistical analyses, including correlation and regression models, were applied to explore relationships and identify factors influencing clinical decision-making. Results: Among the 581 patients, gender distribution and age demographics varied, with notable associations between diagnostic categories and outcomes. Survivors exhibited lower PIM 3 scores compared to nonsurvivors. Probability scores related to outcomes revealed distinct patterns, emphasizing the predictive utility of the PIM 3 score. Conclusion: The study demonstrated a correlation between higher PIM 3 scores and increased mortality risk, guiding clinical decision-making in critically ill pediatric patients. Bridging theory and practice, the findings provide valuable insights for enhancing bedside decision-making and improving the quality of care. Acknowledging contextual factors is crucial for a comprehensive understanding of decision-making processes.